Our Ohonua: Post-disaster Revitalization Urban Design Concept for Eua Island, Tonga - Faisal, Aletta Prudence Asyifa; Ayuningtyas, Qonita; Maulida, Farah Vicka (RUAS, 2023)
The Kingdom of Tonga experienced a tsunami in 2022 after an underwater volcanic eruption. 'Eua Island suffered extensive damage, with 143 buildings affected. The buildings in Ohonua City experienced the highest impact. This study aims to develop an urban design concept for post-disaster revitalization in Ohonua City, in line with the ethos of matriarchy, kinship, and community. The proposed design aims to provide shelter, reduce disaster risks, and contribute to the redevelopment and economy of the city. This study examines the risks of location, cultural context, and its potential for tourism, as well as various challenges, such as migration, education, and limited health facilities. The research uses qualitative methods with community-based design, which combines site and context analysis, spatial analysis, and stakeholder analysis. The final result presents a comprehensive urban design concept for post-disaster revitalization in Ohonua Town, 'Eua Island, emphasizing a community-based approach.